EFEKTIVITAS PENGGUNAAN MEDIA PIANIKA SEBAGAI PENINGKATAN KESADARAN NILAI BUDAYA PADA LAGU DAERAH - Hidayah, Aulia Nurul; Mayariah, Alya; Wijayanto, Wasis (Yayasan Amanah Nur Aman, 2025)
This study aims to determine the effectiveness of the use of piano musical instrument media in increasing students' awareness of local cultural values through regional songs, especially the song